Renal histological findings in a patient with acute renal injury associated with purpura fulminans: a case report - Martins,Julia Izadora da Silva (2019)
ABSTRACT Introduction: Purpura fulminans (PF) is a rapid progressive thrombotic disease in which hemorrhagic infarction of the skin and disseminated intravascular coagulation (DIC) occurs. It can potentially cause acute kidney injury (AKI). However, there is no description in the medical literature of renal histological findings of PF. Case report: A 20-year-old female patient, previously healthy, was admitted to the emergency department (ED) with odynophagia, fever, generalized myalgia and anuria, which evolved with the appearance of purpuric plaques on the face and limbs. She required dialysis on admission. Laboratorial tests showed anemia, leukocytosis, thrombocytopenia, and elevation of lactic dehydrogenase (LDH). The purpuric lesions became bullous with ruptures and then necrotic and erosive, reaching the dermis, subcutaneous tissue and musculature, until bone exposure. There was no improvement with initial antibiotic therapy aimed at the treatment of meningococcemia. Thrombotic microangiopathy (TMA) and PF were then suspected. The patient remained in daily dialysis, requiring plasmapheresis. After sustained improvement of the thrombocytopenia, she underwent renal biopsy, which was not compatible with TMA, characterizing possible PF. A complete recovery of the renal function was achieved and cutaneous sequels were treated with grafts. Conclusion: When thrombotic and hemorrhagic phenomena overlap, obtaining a renal biopsy can be difficult. However, in the presented case, the biopsy allowed the exclusion of AKI caused by TMA, presenting for the first time, histological findings compatible with PF.